Genome resequencing and analysis of D-lactic acid fermentation ability of Leuconostoc mesenteroides subsp. mesenteroides ATCC 8293 - Kim, Ji Won; Choi, Bo Hyun; Jung, Jin Ho; Yuan, Xiaofang; Kim, Ju Min; Lee, Pyung Cheon (Process Biochemistry, 2018)
Genome resequencing of D-lactic acid-producing Leuconostoc mesenteroides ATCC 8293 revealed 28 base errors in the version published in the 2017. Based on the revised genome annotation, four genes encoding putative D-lactate dehydrogenases were identified. The transcriptional expression of each gene was analyzed at different growth phases and the functionality of each gene was studied in Escherichia coli. Bioreactor studies indicated that L. mesenteroides ATCC 8293 produced D-lactic acid and ethanol at a ratio of 1.7:1 (g/g) regardless of the glucose concentration.
Keywords: D-lactate dehydrogenase; D-Lactic acid; Genes encoding; Genome annotation; Glucose concentration; Growth phasis; Leuconostoc mesenteroides; Resequencing; D-Lactic acid; Fermentation; Leuconostoc mesenteroides; Resequencing